Microbial transformation of zearalenone to a zearalenone sulfate. - el-Sharkaway, S H (1991)
The conversion of zearalenone by various microorganisms was studied. A new polar metabolite was formed in addition to alpha- and beta-zearalenols. The structure of the new metabolite was determined as zearalenone-4-O-sulfate conjugate on the basis of enzymatic and acid hydrolysis, followed by mass spectrometry, nuclear magnetic resonance, and infrared spectroscopic analysis. The results obtained demonstrate that Rhizopus arrhizus catalyzes sulfation of zearalenone at the C-4 hydroxyl group.